2023
DOI: 10.1177/10690727231179195
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Perceived Strength Supports Both From Organization and Supervisor to Performances: The Roles of Strengths-Based Climate and Meaningful Task

Abstract: Although employee strengths use has gained popularity in academia and practice, our understanding of its effective application for maximizing employee performance remains insufficient. This study investigates the interaction between perceived organizational and supervisor support for strengths use and employees’ strengths-based psychological climate and job performance. Using multi-wave data from 241 employee–supervisor dyads, the results of polynomial regression equations with a response surface analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, organizations can promote employees' SUT and SUR by supporting strengths use and creating a strengthbased climate. Researchers have indicated that organizational support for strengths use has a positive impact on employees' strengths use and leads to various desirable outcomes for organizations (Bakker and van Woerkom, 2018;Hai and Park, 2023). By providing strengthbased interventions and adequate support for employees to exhibit SUT and SUR, CMS 18,4 organizations can continuously develop their employees' role breadth self-efficacy and achieve substantial improvement in job performance.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, organizations can promote employees' SUT and SUR by supporting strengths use and creating a strengthbased climate. Researchers have indicated that organizational support for strengths use has a positive impact on employees' strengths use and leads to various desirable outcomes for organizations (Bakker and van Woerkom, 2018;Hai and Park, 2023). By providing strengthbased interventions and adequate support for employees to exhibit SUT and SUR, CMS 18,4 organizations can continuously develop their employees' role breadth self-efficacy and achieve substantial improvement in job performance.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Existing literature has shown that strengths use affects important individual outcomes, including occupational health-related outcomes such as employee well-being (Bakker et al, 2019), attitudinal outcomes such as job satisfaction (Lavy and Littman-Ovadia, 2017) and behavioral outcomes such as work engagement and productivity (Littman-Ovadia et al, 2017;Liu et al, 2022). Moreover, organizations can effectively improve employees' productivity and decrease absenteeism by CMS 18,4 1194 supporting employees' strengths use (Hai and Park, 2023;van Woerkom et al, 2016a). Considering the critical role of strengths use in the workplace, further investigations in an organizational context may offer valuable theoretical and practical implications for scholars and practitioners.…”
Section: Introductionmentioning
confidence: 99%